Uso da web pelos bancos: comércio eletrônico nos serviços bancários - Diniz, Eduardo Henrique (2000)
Electronic commerce has the power to change business and the relationship between companies and their clients, suppliers and partners. Looking at the astonishing growth of Internet and the Web, companies are stiU leaming how to use electronic commerce in their business processes as well as in strategies to integrate themselves both internally and externally. Banks have since long been among the companies with the highest leveI of information technology spending in order to support their processes, to reach business efficiency and improve the quality of banking services. Being originated in the technological convergence of computing and telecommunications, electronic commerce open great opportunities to banks, which have been looking for effective ways to offer off-branch banking services for decades. The importance of electronic commerce evolution to banks is even more relevant if it is considered that there is no commerce without payment and they are the main players to keep a trustful and flexible payment system. Therefore, the growing use of the Web and the Internet by banks implies also the consolidation of electronic commerce, either by their importance in controlling the payment system or the trust they mean to electronic fund transfer systems users. This work intends to create ways to evaluate the evolution of electronic commerce in banking services and the diffusion of Web use among banks. Since banks can use the Web to release information, deliver banking products and services and improve customer relationship, Web site analysis, surveys and interviews were taken to identify direction, rate, determinants and implications of Web use evolution among banks.